2021
DOI: 10.1155/2021/5527475
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Aspirin Eugenol Ester on Oxidative Stress to PC12 Cells Stimulated with H2O2 through Regulating PI3K/Akt Signal Pathway

Abstract: Aspirin eugenol ester (AEE) is a new pharmaceutical compound esterified by aspirin and eugenol, which has anti-inflammatory, antioxidant, and other pharmacological activities. This study is aimed at identifying the protective effect of AEE against H2O2-induced apoptosis in rat adrenal pheochromocytoma PC12 cells and the possible mechanisms. The results of cell viability assay showed that AEE could increase the viability of PC12 cells stimulated by H2O2, while AEE alone had no significant effect on the viabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…In this study, we also found GC inhibited the expression of SOD1, SOD2, GR, GPX1, and CAT to activate oxidative stress. According to other reports, GDF15/AKT/mTOR signaling is closely related to oxidative stress, wherein the activation of this signaling could suppress ROS accumulation [ 19 – 21 , 23 , 29 , 48 , 49 ]. In our study, D7 treatment was observed to inhibit the GC-induced oxidative stress by restoring the expression levels of SOD1, SOD2, CAT, and GPX.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we also found GC inhibited the expression of SOD1, SOD2, GR, GPX1, and CAT to activate oxidative stress. According to other reports, GDF15/AKT/mTOR signaling is closely related to oxidative stress, wherein the activation of this signaling could suppress ROS accumulation [ 19 – 21 , 23 , 29 , 48 , 49 ]. In our study, D7 treatment was observed to inhibit the GC-induced oxidative stress by restoring the expression levels of SOD1, SOD2, CAT, and GPX.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, for several other types of cells, the AKT/mammalian target of rapamycin (mTOR) pathway acts downstream of GDF, and GDF15 could promote the survival and proliferation of cells via the activation of AKT/mTOR signaling pathway [26][27][28]. At the same time, the AKT/mTOR signaling pathway is closely associated with ROS, as its activation protects cells from ROS accumulation and restores the balance of ROS [29,30]. Nonetheless, the mechanisms through which GDF15/AKT/ mTOR signaling mediates the pathophysiological changes in association with SONFH and whether this signaling pathway can restore the redox balance in BMSCs under GC conditions are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Under normal physiological conditions, the antioxidant enzymes work to maintain the redox balance of the body and neutralize rampaging free radical and thus reducing its capacity to damage. They act as radical scavenger, hydrogen donor, electron donor, peroxide decomposer, singlet oxygen quencher, and synergist (23)(24)(25) . At the molecular levels, glutathione system is the mother of all antioxidants, the master detoxifier and maestro of the immune system.…”
Section: Parametersmentioning
confidence: 99%
“…When cells are stimulated by H 2 O 2 , oxidative stress occurs, and the body produces too much highly reactive molecules such as reactive oxygen species (ROS). ROS in the body mainly include hydroxyl radicals, superoxide anions and singlet oxygen [28,29] . Excessive production of ROS is one of the main causes of oxidative stress [30,31] .…”
Section: Introductionmentioning
confidence: 99%
“…ROS in the body mainly include hydroxyl radicals, superoxide anions and singlet oxygen. [28,29] Excessive production of ROS is one of the main causes of oxidative stress. [30,31] Normal levels of ROS help maintain normal cellular function.…”
Section: Introductionmentioning
confidence: 99%